Retinal vessel abnormalities predict coronary artery diseases. (May 2013) - Tabatabaee, A; Asharin, MR; Dehghan, MH; Pourbehi, MR; Nasiri-Ahmadabadi, M; Assadi, M
Background: There are limited data supporting an association between retinal microvascular changes and cardiovascular mortality, but there is no convincing evidence of an independent or direct association with atherosclerosis in coronary artery disease (CAD) patients. The present study examines the relationship between retinal microvascular changes and angiographic findings. Methods: Patients who were candidates for angiography were, at first, referred to the ophthalmology department for the determination of the severity of retinal atherosclerosis based on the Scheie classification. Angiography was carried out afterwards. Each patient completed a questionnaire, also providing information on risk factors. For each patient, the Gensini score was calculated using angiography findings. Results: A total of 168 patients (99 males and 69 females) with a mean age of 55.3±11.9 years were included in this study. The results show a significant association between CAD severity and retinal artery atherosclerosis (r = 0.47, p = 0.0001). In multiple regression analyses with CAD severity (using Gensini scoring) as a dependent variable, we observed a significant association between atherosclerosis scores based on Scheie criteria (β=0.31, p<0.0001), diabetes mellitus (DM) (β=0.29, p<0.0001), hypertension (β=0.23, p<0.0001), smoking (β=0.20, p<0.0001), and age (β=0.15, p<0.0001). Conclusions: The results demonstrate that fundoscopic changes might be a predictor of CADs. However, more well-designed studies to verify these results are still needed.